Plasminogen activator inhibitor-1 (PAI-1) is anti-fibrogenic in human inflammatory cardiomyopathy. (14th October 2021) - Baumeier, C; Escher, F; Pietsch, H; Aleshcheva, G; Schultheiss, H P
Abstract: Background/Introduction: Preclinical data indicate that plasminogen activator inhibitor-1 (PAI-1) is cardioprotective by repressing cardiac fibrosis through TGF-β and plasminogen mediated pathways. In addition it is linked to the recruitment and polarization of non-classical M2 macrophages in cancer. Purpose: The role of cardiac PAI-1 in fibrogenesis and macrophage polarization is investigated in patients with dilated cardiomyopathy (DCM) and inflammatory dilated cardiomyopathy (DCMi). Methods: We retrospectively analyzed endomyocardial biopsies (EMBs) of patients with DCM (n=27) and DCMi (n=149) for PAI-1 expression, number of activated myofibroblasts and M1/M2 macrophage polarization. Results: Patients with high-grade DCMi (DCMi-high, CD3+ lymphocytes >30 cells/mm 2 ) had significantly increased PAI-1 levels compared to DCM and low grade DCMi patients (DCMi-low, CD3+ lymphocytes = 14 - 30 cells/mm 2 ) (15.5±0.4% vs. 1.0±0.1% and 4.0±0.1%, p≤0.001). Elevated PAI-1 expression in DCMi-high subjects was accompanied by a reduced number of alpha smooth muscle actin (α-SMA) positive myofibroblasts and an increased number of CD16+ CD68+ M2 macrophages, indicating anti-fibrogenic and M2 macrophage-favoring properties of PAI-1 in DCMi. Conclusion: Our findings give evidence that elevated expression of PAI-1 suppresses cardiac fibrosis and promotes M2 macrophage polarization. Thus, PAI-1 could serve as a potential prognostic biomarker of cardiac fibrosis and inflammation, as well as possible therapeutic target in inflammatory cardiomyopathies. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): ERA-Net on Cardiovascular Diseases (ERA-CVD) of the German Research Foundation (DFG)Transregional Collaborative Research Center "Inflammatory Cardiomyopathy-Molecular Pathogenesis and Therapy"